PERUBAHAN LUAS HUTAN MANGROVE DI PULAU KEMUJAN TAMAN NASIONAL KARIMUNJAWA - Suryanti Ign; Boedi Hendarto; Dhaud Anggoro (LPPM Universitas Pekalongan, 2011)
Karimun Island is one of the islands with the potential of natural resources is one of the verylarge which is a mangrove forest on the island Kemujan. Human activities and tourismactivities tend to threaten the existence of mangrove forest on the island Kemujan.Information changes in land and development of human activities necessary for sustainablemanagement of mangrove forests. This study aims to determine the level of mangrove forestcover in the island Kemujan, knowing that human activity significantly affects the conditionof mangrove forests Kemujan Island National Park Karimunjawa. The study was conducted in 2 phases: a preliminary study in August and the last study in December 2009. The methodused in this study is the imaging method of observation and mapping, the research conductedto observe the phenomenon in the field to get actual data related to materials research. Dataobtained from satellite image analysis and determination of the cause of the significant factorsprocessed by SEM. As a result of image interpretation, in 1991, 2001 and 2009 found thatisland Kemujan gradually changing area. In 1991, the area is 11.734 ha kemujan whichgradually changed to 12.617 hectares in 2001 to 2009 by 11.177 HA. The main reason thesechanges based on public perception derives from public activities such as cleaning ponds,seaweed cultivation and so on.Keyword : mangrove forest, satellite imagery, kemujan island, SEM analysis